Induction motor speed control using reduced-order model. (2nd October 2018) - Sabir, A.; Ibrir, S.
ABSTRACT: Induction machines have a highly nonlinear model with only partial state information. The unavailability of all states and the presence of unknown disturbances make controller design and proving closed-loop stability challenging tasks. In this paper, we present a control scheme for induction motor speed control using a reduced, second-order model. The model greatly simplifies the control structure and its stability analysis. Current and speed measurements are used while the unknown flux and load torque are estimated using observers. The closed-loop stability of the observer-based control structure is established using Lyapunov's analysis. Simulation studies carried out on a 50 HP induction motor driven by a three-phase inverter show that the proposed controller achieves good speed control for both the regulation and tracking test cases under unknown disturbance.